How to Implement the Development of Early Detection Instruments for the Development of Religious and Moral Values of Children Aged 5-6 Years ? - Ida Komalasari; Risbon Sianturi; Taopik Rahman (CV. Rayyan Dwi Bharata, 2023)
In thus day and age, the Indonesian nation is experiencing a crisis that is so influential, namely a crisis of character. Where there are many deviations from social norm, legar norm, and even religios norms. The inculcation of religious and moral values from an early age through early childhood education institutions is very important to be carried out consistently and continuously, bearing in mind that there will be a lot of immoral behavior in society due to the weakness of the moral education system in schools. This study aims to describe the planning, pattern of implementation and evaluation of the inculcation of religious and moral values for children aged 5-6 years at Pertiwi DWP Kindergarten, Tasikmalaya City. This research method uses a descriptive qualitative method. Data collection was carried out using observation techniques, interviews, and documentation studies. The results showed that of the 7 children studied, on average it could be said to have developed as expected. This can be seen from several indicators of the development of religious and moral values that have been achieved.